2016
DOI: 10.1016/j.geomphys.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Parallel transport on principal bundles over stacks

Abstract: a b s t r a c tIn this paper we introduce a notion of parallel transport for principal bundles with connections over differentiable stacks. We show that principal bundles with connections over stacks can be recovered from their parallel transport thereby extending the results of Barrett, Caetano and Picken, and Schreiber and Waldorf from manifolds to stacks.In the process of proving our main result we simplify Schreiber and Waldorf's original definition of a transport functor for principal bundles with connect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…in the sense of [CLW16]. They showed that such functors are the same as principal G-bundles with connection.…”
Section: The Thin Fundamental 2-groupoidmentioning
confidence: 99%
See 1 more Smart Citation
“…in the sense of [CLW16]. They showed that such functors are the same as principal G-bundles with connection.…”
Section: The Thin Fundamental 2-groupoidmentioning
confidence: 99%
“…These two constructions give an equivalence of categories. Stated in different terms this result is originally due to[Bar90], but using categorical language this statement appears in[SW09,CLW16].Theorem 4.1. The procedure above defines an equivalence of categories Bun 1 ∇ (M, G) ∼ = Trans 1 (M, G), i.e.…”
mentioning
confidence: 99%
“…All of the previous developments provided multiple insights that paved the way towards a rigorous mathematical formulation of the reconstruction theorem of gauge fields in terms of their holonomy homomorphisms from a group of based loops on a manifold to a Lie group G. Different proofs of the reconstruction theorem appeared in [Bar89,Bar91], [Lew93], [Haj93], [CP94], leading to subsequent mathematical developments of the notion of groups of based loops [Ful94], [Gib97], [Woo97], [MP02], [SW09,CLW16], [Tla16]. Somewhat independent, but equally important, are the works of Gross [Gro85], who gave an analytic proof of the equivalence between the Yang-Mills and Maldestam-Bia lynicki-Birula equations, and Morrison [Mor91], who gave a characterization of connections on principal bundles over oriented Riemannian surfaces satisfying the Yang-Mills equations in terms of their corresponding holonomies.…”
Section: Brief Surveymentioning
confidence: 99%
“…In particular, the structure of a connection on Lie groupoids and for principal bundles over Lie groupoids as well as its associated geometric and algebraic properties have been discussed by several authors. Among them [LGTX2,BX,B,CM,CLW] are particularly relevant for this article. For example, the articles [LGTX2] and [CM] study Chern-Weil theory on Lie groupoids via the de Rham cohomology defined using simplicial manifolds associated to the groupoid nerves.…”
Section: Introductionmentioning
confidence: 99%